How Multitasking during Video Content Decreases Ad Effectiveness: The Roles of Task Relevance, Video Involvement, and Visual Attention - Sun, Shuoya; Wojdynski, Bartosz; Binford, Matthew T.; Ramachandran, Charan (Journal of promotion management, 2022)
In a 3 (secondary task: none, related, unrelated) x 2 (ad-video congruence: high/low) between-subjects eye-tracking experiment, participants (N = 153) watched a 9-minute video documentary segment containing one mid-roll video ad while their visual attention to the screen was recorded. Participants in two-thirds of the conditions also read two online articles on a mobile device during the video. Results show effects for both multitasking and task relatedness on attention to the ad and attitudes toward the ad, through distinct pathways. Specifically, multitasking reduced attention to the ad. Moreover, multitasking on an unrelated task lowered attitudes toward the ad by decreasing program involvement and the subsequent attention to the ad.